INTERPRETATION OF OXYGEN –18 ISOTOPE IN SULPHATE FROM DEEP GROUNDWATER IN JAKARTA AREA - E. Ristin Pujiindiyati; Wandowo Wandowo; Zainal Abidin (Indonesian Journal of Chemistry, 2007)
It has been done a determination of d 18O (SO42-) and d 18O (H2O) value from Jakarta deep groundwater with depth 40-140 m. The aim of this research is to know some procesess influencing the composition of oxygen isotope in groundwater sulphate. A method commonly used to determine d 18O (H2O) value is according to Epstein-Mayeda. CO2 gas resulted from   equilibration process between water sample and CO2 gas standard in which oxygen isotopic reaction has occurred, is injected to mass spectrometer. For determination of d 18O (SO42-) value, Rafter method is used. CO2 gas released from reducing sulphate of water sample with graphite is injected to mass spectrometer. The results of d 18O (H2O) values obtained in this experiment have a narrow range from  -5,04 0/00 to  -6,65 0/00 SMOW whereas their d18O (SO42-) values have a wider range from +8,3 0/00 to +17,4 0/00 SMOW.  The more constant values of d 18O (H2O) performed that evaporation effects might not occur.  Based on the similarity between d18O (SO42-) values of deep groundwater and that of marine evaporite sulphate rocks, it is supposed that sulphate of Jakarta deep groundwater was derived from dissolution of this rocks. There was an indication of seawater intrusion around Pejagalan and Kamal Muara Penjaringan area based on the similarity between their d18O (SO42-) values and d18O (SO42-) of modern seawater.  The contribution of oxygen from water in sulphide oxidation reaction ranged 0% to 12% suggesting that oxygen in deep groundwater sulphate was mainly derived from atmospheric molecular oxygen.